2019
DOI: 10.1038/s41598-019-53394-w
|View full text |Cite
|
Sign up to set email alerts
|

Plant sphingolipids promote extracellular vesicle release and alleviate amyloid-β pathologies in a mouse model of Alzheimer’s disease

Abstract: The accumulation of amyloid-β protein (Aβ) in brain is linked to the early pathogenesis of Alzheimer’s disease (AD). We previously reported that neuron-derived exosomes promote Aβ clearance in the brains of amyloid precursor protein transgenic mice and that exosome production is modulated by ceramide metabolism. Here, we demonstrate that plant ceramides derived from Amorphophallus konjac, as well as animal-derived ceramides, enhanced production of extracellular vesicles (EVs) in neuronal cultures. Oral adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 56 publications
0
46
0
Order By: Relevance
“…9,22 In addition, in our previous study, we found that Cer extracted from the higher plant Amorphophallus konjac increased exosome release from neuroblastoma SH-SY5Y cells. 39 Furthermore, oral administration of plant Cer to human APP SweInd transgenic mice resulted in increased neuronal exosomes in the blood and brain, as well as decreased Aß levels and amyloid depositions in the brain. 39 Here, we verified that Cer addition moderates the abnormal accumulation of Aß in cells through LAPTM4B ( Figure 6), suggesting that Cer/LAPTM4Bdependent vesicle trafficking and exosomal efflux can modulate cellular Aß levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,22 In addition, in our previous study, we found that Cer extracted from the higher plant Amorphophallus konjac increased exosome release from neuroblastoma SH-SY5Y cells. 39 Furthermore, oral administration of plant Cer to human APP SweInd transgenic mice resulted in increased neuronal exosomes in the blood and brain, as well as decreased Aß levels and amyloid depositions in the brain. 39 Here, we verified that Cer addition moderates the abnormal accumulation of Aß in cells through LAPTM4B ( Figure 6), suggesting that Cer/LAPTM4Bdependent vesicle trafficking and exosomal efflux can modulate cellular Aß levels.…”
Section: Discussionmentioning
confidence: 99%
“…39 Furthermore, oral administration of plant Cer to human APP SweInd transgenic mice resulted in increased neuronal exosomes in the blood and brain, as well as decreased Aß levels and amyloid depositions in the brain. 39 Here, we verified that Cer addition moderates the abnormal accumulation of Aß in cells through LAPTM4B ( Figure 6), suggesting that Cer/LAPTM4Bdependent vesicle trafficking and exosomal efflux can modulate cellular Aß levels. The expression level and activity of acid ceramidase are disrupted in the brains of AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The pathology of AD begins with the formation of amyloid plaques (senile plaques) due to the accumulation of amyloid-β protein (Aβ) in the brain [ 18 , 19 ]. In a previous study, we reported that oral administration of GlcCer extracted from Amorphophallus Konjac to an AD mouse model markedly decreased Aβ accumulation, suppressed amyloid deposition in the brain, and improved cognitive ability in a Y-maze learning task [ 20 , 21 ]. In addition, after plant GlcCer administration, levels of neuronal exosomes, a type of extracellular vesicle (EV), were elevated in blood and brain tissues [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we reported that oral administration of GlcCer extracted from Amorphophallus Konjac to an AD mouse model markedly decreased Aβ accumulation, suppressed amyloid deposition in the brain, and improved cognitive ability in a Y-maze learning task [ 20 , 21 ]. In addition, after plant GlcCer administration, levels of neuronal exosomes, a type of extracellular vesicle (EV), were elevated in blood and brain tissues [ 21 ]. Our previous studies demonstrated that neuronal exosomes promote Aβ clearance, and plant ceramides enhance production of exosomes in neuronal cells [ 22 , 23 ], suggesting that plant ceramides might affect exosome production within the brain.…”
Section: Introductionmentioning
confidence: 99%
“…However, as a consequence, this might implicate a role for EVs in the formation of extracellular Aβ plaques. Mechanistically, the interaction between Aβ and the surface of the EVs was shown to be mediated by glycosphingolipids [ 48 , 54 , 55 , 56 ] and the cellular prion protein (PrP C ) [ 49 ] present on the EV membrane. Furthermore, it was shown that the hippocampal administration of EVs isolated from N2a cells [ 54 ] or mouse primary neurons [ 55 ] in APP SweInd mice causes a reduction in total Aβ levels and the amount of thioflavin-S positive plaques, which was attributed to an EV-associated Aβ uptake by microglia [ 54 ].…”
Section: The Role Of Evs In Admentioning
confidence: 99%